Degradation of black phosphorus is contingent on UV–blue light exposure - Taimur Ahmed (Nature Portfolio, 2017)
Black phosphorous degradation: UV light contributes the most to photo-oxidation The ultraviolet component of the light spectrum contributes significantly to the ambient degradation of ultra-thin black phosphorous. A team led by Sumeet Walia at RMIT University in Melbourne investigated the deterioration of layered black phosphorous under environmental conditions, upon exposure to individual wavelengths of light at progressive time durations. Morphological variations, indicative of material degradation, were found to be most prominent under exposure to 280 nm light, followed by 455 nm light. Conversely, longer wavelengths did not induce any discernible photo-oxidation. These results indicate that ultraviolet light is readily absorbed by black phosphorous resulting in a substantial decline of its electronic properties, whereas blue light causes less severe surface deterioration. An ultraviolet-deficient environment could therefore be instrumental to preventing black phosphorous photo-oxidation, and could be as effective as surface passivation by means of encapsulating layers.